A study of predicting factors and medical expulsion therapy for solitory lower ureteric calculi - Nagapurkar, Nagesh S.; A. Patel, Viquar (International Journal of Research in Medical Sciences, 2024)
Background: The aim of our study is to evaluate the outcome of medical expulsion therapy (MET) for lower ureteric calculi and asses the clinical, laboratory and radiological factors that predict conservative approach. We evaluated the efficacy of combined drug therapy with alpha 1 adrenergic receptor antagonist tamsulosin and corticosteroid deflazacort for MET therapy for lower ureteric calculi. Methods: A prospective randomized control study was conducted in the department of surgery urology wing on out patients (OPD) basis at IIMSR Medical College Warudi District Jalna a tertiary referral center after approval from the ethical committee. The study conducted between 01 January 2020 to 31 December 2023 over period of three years. Total 76 cases included with the age 18 years old and above. The patients were examined weekly with ultrasonography and kidney ureter bladder (KUB) for 4 weeks and the stone expulsion rate and time, pain episodes during follow-up period, total diclofenac dosage and the need for any intervention was noted close monitoring and timely follow up is mandatory counselling and selection of patient is key factor. Results: Stone expulsion with patients on MET was 84% which is higher as compare to another group 57%. Conclusions: Medical therapy with a combination of α-adrenergic blocker and corticosteroid is associated with good stone expulsion rates and should be considered in all patients with lower ureteral stones of size less than 10 mm who are not having any contraindications for medical therapy provided close monitoring and timely follow up is mandatory counselling and selection of patient is key factor.